Understanding bioinformatics - Zvelebil, Marketa J. (Garland Science/Taylor & Francis Group, 2008)
The material is organized into seven sections--background basics, sequence alignments, evolutionary processes, genome characteristics, secondary structures, tertiary structures, cells and organisms--the majority of which contain both applications chapters, focusing on the main concepts, and theory chapters providing greater detail and the underlying mathematics. Illustrated throughout with charts, diagrams, and tables.